2018
DOI: 10.1016/j.cell.2018.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Segregation Controls Macrophage Phagocytosis of Antibody-Opsonized Targets

Abstract: Macrophages protect the body from damage and disease by targeting antibody-opsonized cells for phagocytosis. Though antibodies can be raised against antigens with diverse structures, shapes, and sizes, it is unclear why some are more effective at triggering immune responses than others. Here, we define an antigen height threshold that regulates phagocytosis of both engineered and cancer-specific antigens by macrophages. Using a reconstituted model of antibody-opsonized target cells, we find that phagocytosis i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 72 publications
4
103
0
Order By: Relevance
“…Importantly, we adopted BSLB as a scalable platform to analyze SE by flow cytometry and mass spectroscopy. BSLB have been used previously to demonstrate activity of purified MHC proteins (30), detect weak protein 5 interactions (20) and determine biophysical requirements for phagocytosis (31). We have also used BSLB to calibrate site densities of recombinant proteins attached to SLB by flow cytometry (32) and for bulk functional assays (6).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we adopted BSLB as a scalable platform to analyze SE by flow cytometry and mass spectroscopy. BSLB have been used previously to demonstrate activity of purified MHC proteins (30), detect weak protein 5 interactions (20) and determine biophysical requirements for phagocytosis (31). We have also used BSLB to calibrate site densities of recombinant proteins attached to SLB by flow cytometry (32) and for bulk functional assays (6).…”
Section: Discussionmentioning
confidence: 99%
“…1Ai,upper) (Oldenborg et al, 2000;Tsai and Discher, 2008;Weiskopf et al, 2013;Chowdhury et al, 2019). Phagocytosisactivating interactions occur in parallel, with the clearest pathway involving Fc-receptors (FcRs) that bind and organize IgG-type antibodies on a target cell (Lopes et al, 2017;Bakalar et al, 2018). IgG-opsonized targets activate the actomyosin tension that makes phagocytic internalization a highly efficient processespecially when CD47 is absent from a phagocytic target or else blocked with anti-CD47, including Fc-deficient F(ab′) 2 (Tsai and Discher, 2008;Sosale et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that macrophage phagocytosis is dependent on size-based segregation of the inhibitory phosphatase CD45 from the antibody-bound FcγR (Bakalar et al, 2018). Specifically, FcγR binding to an antibody targeting the membrane, which creates a membrane-membrane gap of approximately 12 nm (estimated from crystal structures (Bakalar et al, 2018;Lu et al, 2011)), results in efficient phagocytosis due to maximum exclusion of CD45 (Bakalar et al, 2018). This activating interface gap almost perfectly matches with the size of SIRPα-CD47 interaction (~13 nm estimated by crystal structure (Hatherley et al, 2009)).…”
Section: Sirpα-cd47 Binding Drives Exclusion Of Cd45 and Co-localizesmentioning
confidence: 99%
“…How do macrophages integrate conflicting activating and inhibitory signals? Recent work on macrophage FcγR activation has helped to clarify the molecular mechanisms responsible for antibody-dependent phagocytosis (Bakalar et al, 2018;Freeman et al, 2016), but how CD47 binding activates SIRPα and how SIRPα ITIMs counteract FcγR signaling remain active areas of research. Recently, Morrissey et al demonstrated that SIRPα-CD47 binding inhibits macrophage integrin activation and that artificially stimulating integrins recovers some of the impaired phagocytosis (Morrissey & Vale, 2019).…”
Section: Introductionmentioning
confidence: 99%